The ABCs of flower development: mutational analysis of AP1/FUL‐like genes in rice provides evidence for a homeotic (A)‐function in grasses. (4th February 2017) - Wu, Feng; Shi, Xiaowei; Lin, Xuelei; Liu, Yuan; Chong, Kang; Theißen, Günter; Meng, Zheng
Summary: The well‐known ABC model describes the combinatorial interaction of homeotic genes in specifying floral organ identities. While the B‐ and C‐functions are highly conserved throughout flowering plants and even in gymnosperms, the A‐function, which specifies the identity of perianth organs (sepals and petals in eudicots), remains controversial. One reason for this is that in most plants that have been investigated thus far, with Arabidopsis being a remarkable exception, one does not find recessive mutants in which the identity of both types of perianth organs is affected. Here we report a comprehensive mutational analysis of all four members of the AP1 / FUL ‐like subfamily of MADS‐box genes in rice ( Oryza sativa ). We demonstrate that OsMADS14 and OsMADS15, in addition to their function of specifying meristem identity, are also required to specify palea and lodicule identities. Because these two grass‐specific organs are very likely homologous to sepals and petals of eudicots, respectively, we conclude that there is a floral homeotic (A)‐function in rice as defined previously. Together with other recent findings, our data suggest that AP1 / FUL ‐like genes were independently recruited to fulfil the (A)‐function in grasses and some eudicots, even though other scenarios cannot be excluded and are discussed. Significance Statement: Although the well‐known ABC model for specifying floral whorl identity was published 25 years ago, the A‐function (specifying sepals and petals) remains highly controversial. Here we functionally characterized all rice AP1 / FUL subfamily genes and provide strong evidence that, in addition to their ancestral function in specifying floral meristem identity, two AP/FUL genes act together to fulfill an (A)‐function, specifying palea and lodicule identities.